Trabalho infantil no Brasil: determinantes da redução entre 2003 e 2011 e efeitos sobre a escolaridade e o rendimento na vida adulta - Paiva, James Souza de (2013)
The hypothesis that child labor impacts future income generation negatively, for it harms the formal acquisition of education, is widely accepted by the existing literature on this issue. However, some researchers agree that labor might be beneficial to teenagers once they can develop skills, acquire job experience, or even help them to afford their own education acquisition. Thus, the main goal of this study is to assess if there is an age which the negative impact of the early access to the labor market over income and the conclusion of high school, during the adulthood of Brazilian people, becomes positive. To do so, PNADs (Pesquisas Nacionais de Amostra de Domicílios), a National Census of Household Samples, issues 1992 to 2011, were utilized plus the employment of an econometric technique called pseudo-panel. For this analysis, generations of people born between 1982 and 1991 were observed from the ages 10 to 17 (child labor) and from the ages 20 to 29 (conclusion of high-school & income). The results show that starting at the age of 15, the negative effect of an early access to the labor market over income, between ages 20-29, becomes positive. As per high-school, it was observed that accessing the labor market before the age 15 diminishes the probability for an individual to conclude high school before the age 21. From this age on, labor does not have a negative impact anymore. The second goal of this study is to assess how much of the reduction of the child labor occurrence in Brazil for the past years is due to changes of economic and demographic characteristics of children and families. For these analyses PNADs - National Census of Household Samples, issues 2003 to 2011, were employed plus the methodology of decomposition that divides the variation of child labor into 2 components: (a) changing of the probability of children with the same characteristics (intragroup) to start working – access labor market & (b) changing of the distribution of characteristics (intergroups). The results show that the reduction of the child labor occurrence is due, mainly, to changes on the probabilities. In general terms, the occurrence of child labor took place, more significantly, among individuals of the ages 15 to 17 & household heads with less education. Besides the characteristics mentioned, the reduction between non-white individuals was also significant among individuals from 4-member families. The results show that the reduction of child labor took place, mainly, among children and teenagers from non-white and poor families.